Training for systematic oral examination improves the detection of simulated lesions in the oral mucosa - Simonato, Luciana Estevam; Bueno, Hugo Sobrinho; Cantieri-Debortoli, Daniela Filié; Silva, Melaine Mont’Alverne Lawall; Tomo, Saygo (Journal of Oral Diagnosis, 2025)
Objective: Evaluate the effect of systematic oral examination training on the accuracy of detecting simulated oral lesions among dental surgeons (DDS) and dental students (DS). Methods: Twenty-seven DDS (with >2 years’ practice) and 10 final-year DS were randomized into control and intervention groups. The intervention group attended a lecture on oral cavity anatomy and a systematic examination protocol. Simulated patients, without oral lesions or prostheses, had black dots applied to their mucosa. Participants examined these patients and recorded any detected lesions and their locations. Results: In the intervention group, DDS detected lesions at a median rate of 90%, significantly higher than 75% in controls (p=0.01). Similarly, DS in the intervention group achieved a median detection rate of 90% versus 80% in controls. Furthermore, DDS in the intervention group were significantly more accurate in localizing lesions on the floor of the mouth (p=0.004), right maxillary tuber (p=0.01), upper labial mucosa (p=0.01), and lower jaw right vestibule (p=0.004). Conclusion: Systematic oral examination training significantly enhances the accuracy of simulated oral lesion detection, particularly in critical anatomical regions. These findings support the value of targeted training for improving diagnostic skills among dental practitioners and students.